CONSTRUCT MATHEMATICAL MODELS OF ENGINEERING NETWORKS TO IMPLEMENT IT ON A PERSONAL COMPUTER (Municipal economy of cities (Technical science), 2013)
The way of presentation of piping systems (for example, the gas network) in a mathematical form suitable for implementation on a computer. It is shown that the calculation of pipeline systems can use a wide range of methods and algorithms developed for electric power systems....